Yogyakarta culture technology (Yogyakarta–cultech): Utilizing user-friendly gamification-based platforms to revitalize Yogyakarta's culture in enhancing digital literacy and achieving SDG 11 - Afan Rico Al Rauf (The Journal of City: Branding and Authenticity, 2026)
Background: The development of digital technology provides great opportunities for the preservation and revitalization of local culture, but on the other hand, it also presents challenges in the form of declining interest among the younger generation in regional culture and low digital literacy rooted in local wisdom values. Amidst the tide of globalization and the dominance of popular digital culture, Yogyakarta culture risks being marginalized if it is not adapted to a medium that is relevant to the character of the current generation. To address these issues, an innovation called Yogyakarta Culture Technology (Yogyakarta-Cultech) was developed. This innovation was developed through a digital platform development approach using a system design method based on literature review, user needs analysis, and the use of gamification concepts. Methods: This study adopts a qualitative descriptive development approach to examine the use of a gamification-based digital platform as a strategy for cultural revitalization and the strengthening of city branding authenticity. Data were collected through literature review, needs analysis, and expert validation, and analyzed using thematic qualitative techniques grounded in cultural revitalization, digital literacy, and place branding perspectives. Findings: Yogyakarta-Cultech is a user-friendly and interactive cultural learning platform that integrates gamification elements to increase the participation and interest of the younger generation in Yogyakarta's culture. This platform has main features such as Explore Culture Map, Quiz Time, and Friend Challenge, which encourage exploration and active user engagement. Conclusion: Yogyakarta-Cultech aims not only to revitalize Yogyakarta's culture in the digital space, but also to improve the community's digital literacy in a contextual and sustainable manner. Novelty/Originality of this article: This innovation is expected to contribute to supporting the preservation of local culture, strengthening cultural identity, and achieving Indonesia's 2030 Sustainable Development Goals (SDGs), particularly target 11, which is sustainable cities and communities.